2014
DOI: 10.1016/j.stem.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Intracellular ROS Levels Regulate Airway Basal Stem Cell Homeostasis through Nrf2-Dependent Notch Signaling

Abstract: SUMMARY Airways are exposed to myriad environmental and damaging agents such as reactive oxygen species (ROS), which also have physiological roles as signaling molecules that regulate stem cell function. However, the functional significance of both steady and dynamically changing ROS levels in different stem cell populations, as well as downstream mechanisms that integrate ROS sensing into decisions regarding stem cell homeostasis, are unclear. Here, we show in mouse and human airway basal stem cells (ABSCs) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
234
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(245 citation statements)
references
References 48 publications
10
234
0
1
Order By: Relevance
“…We speculate that there might be epigenetic differences amongst basal cell subpopulations that predict their future behavior, as has been shown in other systems such as the intestine . It has been recently suggested that dynamic reactive oxygen species levels in basal cells can regulate their symmetric versus asymmetric cell division (Paul et al, 2014). It would be interesting to assess whether and how reactive oxygen species levels regulate injury-associated basal cell heterogeneity (Paul et al, 2014).…”
Section: Basal Cellsmentioning
confidence: 99%
“…We speculate that there might be epigenetic differences amongst basal cell subpopulations that predict their future behavior, as has been shown in other systems such as the intestine . It has been recently suggested that dynamic reactive oxygen species levels in basal cells can regulate their symmetric versus asymmetric cell division (Paul et al, 2014). It would be interesting to assess whether and how reactive oxygen species levels regulate injury-associated basal cell heterogeneity (Paul et al, 2014).…”
Section: Basal Cellsmentioning
confidence: 99%
“…Furthermore, a low level of ROS, is not only useful but essential for normal cellular functions (Liochev, 2013). Conversely, high ROS levels are not always associated with senescence as they are sometimes linked to differentiation (Paul et al, 2014).…”
Section: Protective Mechanism and Damage Markersmentioning
confidence: 99%
“…Thus, Nrf2 to Notch crosstalk is functional in the early phase of liver regeneration when hepatocyte self-renewal occurs [42]. Subsequently, this conjoined molecular signaling has been observed in airway basal stem cells, in turn affecting their proliferation and self-renewal states [43]. It could be speculated that protection from endogenous or exogenous stressors and maintenance of vital homeostasis in adult tissue stem cells and their niches could be mediated, at least partially, by directed Nrf2 to Notch1 signaling.…”
Section: Reciprocal Nrf2-notch Transcriptional Regulation In the Hepamentioning
confidence: 99%
“…This crosstalk can probably influence the adaptive defenses of the stem cells and be important for the maintenance of homeostasis of the niche. In addition to hepato-cholagionenesis in adult liver [47,84,85], the airways basal stem cell system for proliferating or self-renewal in the lung [43], enterogenesis in the intestinal crypt [86], adult neurogenesis occurring in the subventricular zone and/or the dentate gyrus of the hippocampus in the central nervous system [15,87,88], dermatogenesis in the skin [17,89,90], osteogenesis in bone [91,92], cell fate determination in hematopoiesis [93,94] and angiogenesis in various tissues [95] might all be valuable settings for further evaluation ( Figure 5A). …”
Section: Lessons From Genetically Engineered Mice Biological Significmentioning
confidence: 99%